2009
DOI: 10.1158/1078-0432.ccr-09-1087
|View full text |Cite
|
Sign up to set email alerts
|

Antiglioma Immunological Memory in Response to Conditional Cytotoxic/Immune-Stimulatory Gene Therapy: Humoral and Cellular Immunity Lead to Tumor Regression

Abstract: Purpose: Glioblastoma multiforme is a deadly primary brain cancer. Because the tumor kills due to recurrences, we tested the hypothesis that a new treatment would lead to immunological memory in a rat model of recurrent glioblastoma multiforme. Experimental Design: We developed a combined treatment using an adenovirus (Ad) expressing fms-like tyrosine kinase-3 ligand (Flt3L), which induces the infiltration of immune cells into the tumor microenvironment, and an Ad expressing herpes simplex virus-1-thymidine ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 48 publications
0
41
0
1
Order By: Relevance
“…Several clinical trials for GMB using DC vaccines have demonstrated cellular and humoral anti-tumor immune responses; and albeit safe, the clinical efficacy of DC vaccination for GBM remains limited (3, 510). Our group has shown that i n situ Ad-Flt3L/TK-mediated immunogene therapy elicits an influx of DCs, macrophages, CD4+ T cells, and CD8+ T cells into the brain tumor microenvironment (17) and stimulates effective anti-GBM immune response resulting in tumor regression and long-lasting CD8+ T cell mediated anti-tumor immunological memory in several mouse and rat orthotopic brain tumor models (16, 18, 2224, 29). Based on these data, a Phase I clinical trial for GBM was recently cleared by the FDA and is slated to commence in 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials for GMB using DC vaccines have demonstrated cellular and humoral anti-tumor immune responses; and albeit safe, the clinical efficacy of DC vaccination for GBM remains limited (3, 510). Our group has shown that i n situ Ad-Flt3L/TK-mediated immunogene therapy elicits an influx of DCs, macrophages, CD4+ T cells, and CD8+ T cells into the brain tumor microenvironment (17) and stimulates effective anti-GBM immune response resulting in tumor regression and long-lasting CD8+ T cell mediated anti-tumor immunological memory in several mouse and rat orthotopic brain tumor models (16, 18, 2224, 29). Based on these data, a Phase I clinical trial for GBM was recently cleared by the FDA and is slated to commence in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of anti-CNS1 antibodies were measured by flow cytometry, described previously (29) and in Supplemental Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…There are a variety of viral-based anti-cancer approaches being explored today for GBM, ranging from immune-targeting antigen-delivery systems (5961) to tumor-targeting suicide gene delivery vectors (62) to directly oncolytic viruses (6365). The latter two strategies classically employ viruses with specific tissue predilections, with the neural preferences for herpes and polioviruses creating roles in glioma (reviewed in (66)).…”
Section: Clinical Applications: Immunotherapeutic Approaches To Gbmmentioning
confidence: 99%
“…RG2 cells (20,000 in 3 µl DMEM) were stereotactically implanted in the right striatum of syngeneic Fisher rats (220–250 g; Harlan Laboratories Inc.) at the coordinates of 1.0 mm anterior and 3.2 mm lateral from the bregma and 6.0 mm ventral from the dura as previously described (16, 31). GL26 cells expressing ovalbumin were prepared as before (32).…”
Section: Methodsmentioning
confidence: 99%